거주자 재실 스케줄을 고려한 주거용 열회수 환기유닛 팬에너지 저감 가능성에 대한 실험 연구 - 바이패스 모드와 실별제어 모드가 적용된 현열교환 환기유닛의 케이스를 중심으로 - 조경주(Kyungjoo Cho); 조동우(Dongwoo Cho) (KIEAE Journal, 2021)
Purpose: Recently in Korea, air quality deterioration due to ultra-fine particles is a social issue. For this reason, many residents have installed high-performance filters in heat recovery ventilators (HRVs) of their houses to eliminate it. Accordingly, the fan power of the HRVs can be increased due to the static pressure increase of the HRVs. One technique to reduce the increased fan power could be application of the by-pass control mode, and another could be the room control mode. In this study, the fan energy savings were presented through field experiments when the ventilation requirement provided for each room through the by-pass mode and the room control mode. Method: First, occupancy schedules were analyzed for calculating the ventilation requirement for each room in an 85m2 apartment house. Second, the fan powers were measured with the practically required ventilation rates according to the occupancy schedules and all room ventilation mode. Third, the fan powers were presented through the field experiments when the by-pass control mode and room control mode were applied with the same experimental conditions. Result: It was analyzed that the fan powers could be reduced by 26~45% when the bypass ventilation mode is used and by 6.4~54.9% when the room control is applied. Therefore, active use of the bypass control mode and room control mode for the HRVs could be effective for building energy reduction. KCI Citation Count: 0